(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The incidence of anthracnose disease was observed lowest in December (10.87%) and highest in July (80.50%) at the three selected betel vine fields of Shalon village in Moulvibazar district. The young stems were found more prone to attack than the old ones. Pathogenicity test showed Colletotrichum dematium and C. gloeosporioides produced characteristic disease symptoms on betel stems. Among them C. dematium is a new document as a pathogen of anthracnose of betel vine. Out of five fungicides, complete inhibition of both the pathogens in vitro occurred with corozole EC (25% propiconazole), folicur EC (25% tebuconazole) and trooper WP (75% tricyclazole). Among the four antagonistic fungi, Penicillium sp. showed more antagonistic potentiality against the pathogens. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20092 Dhaka Univ. J. Biol. Sci. 23(2): 127-133, 2014